Quality Management of Madrasah Diniyah Takmiliyah in the Era of Regional Autonomy (Case Study in Tasikmalaya Regency) - Hakim, Lukman (Jurnal Pendidikan Islam, 2019)
This study aims to investigate the policy implementation on Madrasah Diniyah Takmiliyah (MDT) in the era of regional autonomy in Tasikmalaya regency. This study is qualitative in nature and it applied descriptive method. Data were collected through interview techniques, observation and documentation studies. This study found that educational program policy for MDT in Tasikmalaya was supported by the legal basis issued by regional regulation on religious education. Other findings concern the problem that occurred in the policy implementation. They include: organizational structure was not uniform, educational provider and the communityÂ had not shown the culture that appreciates the importance of quality education, human resource both quality and quantity were not sufficient, infrastructure quality and quantity were inadequate, the curriculum had not met the standard since it was still centralistic and overcrowded, educational quality management had not been implemented by MDT since the management of madrasa was still traditional, the ownership of madrasah was mostly still controlled by the family, the operational budget was limited, social support was low, and local government assistance was limited.Â